2005
DOI: 10.1529/biophysj.104.053736
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Vesicle Quantal Size and Fusion Pore Release in Chromaffin Cell Exocytosis

Abstract: A significant number of exocytosis events recorded with amperometry demonstrate a prespike feature termed a "foot" and this foot has been correlated with messengers released via a transitory fusion pore before full exocytosis. We have compared amperometric spikes with a foot with spikes without a foot at chromaffin cells and found that the probability of detecting a distinct foot event is correlated to the amount of catecholamine released. The mean charge of the spikes with a foot was found to be twice that of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
107
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(117 citation statements)
references
References 58 publications
9
107
1
Order By: Relevance
“…The probability of detecting a foot signal is positively correlated with the quantal size of a vesicle (Amatore et al, 2005). The properties of the spike foot in regards to its height, duration and area were significantly reduced in KO cells (Table 1).…”
Section: Amperometry Reveals Details Of Ldcv Exocytosis In Clc-3 Ko Cmentioning
confidence: 97%
“…The probability of detecting a foot signal is positively correlated with the quantal size of a vesicle (Amatore et al, 2005). The properties of the spike foot in regards to its height, duration and area were significantly reduced in KO cells (Table 1).…”
Section: Amperometry Reveals Details Of Ldcv Exocytosis In Clc-3 Ko Cmentioning
confidence: 97%
“…Careful analysis of these pre-spike events in chromaffin cells has revealed that they are quite common, occurring in approximately 30% of events, and that although their occurrence does not indicate the size of the event, the flux through the corresponding fusion pore correlates with the flux of the entire event (Amatore et al 2009). Feet have been detected both before (Amatore et al 2005) and after (Mellander et al 2012) the spike for a significant number of events leading to a higher total release from the vesicle as measured by the charge released.…”
Section: A Flickering Fusion Pore Might Regulate Quantal Release and mentioning
confidence: 99%
“…These vesicles are morphologically distinct from dense core vesicles in mast and chromaffin cells, a fact that maybe related to the ability of PC12 to continuously reload their vesicles. [65][66][67] Beyond the very origin of this important morphological difference, it must be noted that the observation of these halos in EM micrographs provides a strong support for the co-existence of different compaction domains of chromogranins-catecholamine cations inside of vesicles.…”
Section: Consequence Of the Two-reservoir Nanostructure On Release Kimentioning
confidence: 99%
“…250%. [65][66] However, despite these extremely important changes, the time constants of the current spikes descending branches do not vary significantly for L-DOPA-loaded vesicles compared to controls. This suggests that even if (k diff ρ ) halo /k diff ρ is larger than unity, this gain is more or less compensated by the decrease associated to the presence of the factor 1/(1 + k 4 /k 3 ) in the time constant in Equation 17.…”
Section: Consequence Of the Two-reservoir Nanostructure On Release Kimentioning
confidence: 99%